UI/UX Design Of Website-Based E-Commerce Application Using Lean User Experience Method - Arujisaputra, Erwin Teguh; Heriansyah, Madi; Zamani, Fadli Emsa; Husain, Adam (CV. Generasi Intelektual Digital, 2025)
Tomkids Children's Clothing Store Bandung is a store engaged in the sale of children's clothing in Cimenyan-Bandung Regency. So far, activities in the store can be said to be less than optimal, because the transaction process is still carried out conventionally or buyers come directly to the Tomkids Store. This makes it difficult for customers who live far from the Tomkids Store. Customers find it difficult to find out what information is still offered by the Tomkids Store, therefore a website design is needed that can help increase sales at the Tomkids Store. The method used in designing a website at Toko Tomkids is using the Lean UX model based on the website. From the analysis and design process, a UI/UX E-commerce application will be produced at Toko Tomkids which can help in the promotion and sales process, and make it easier for customers to make online children's clothing purchases. And the data analysis and processing techniques use a questionnaire by giving statements to respondents. To reach respondents, 40 people were selected, consisting of two groups, the first is 20 respondents who are lay with e-commerce and experienced in online shopping. Second, there are 20 respondents who have or have a trading business. The results of this study are in the form of a better and optimal User Interface and User Experience design for the e-commerce application at Toko Tomkids Baju Anak Bandung based on the website. The purpose of designing this application is to display the interface and experience pages so that it can provide information to customers, make orders and also be able to make purchases so that customers can make transactions online.